2012
DOI: 10.1590/s0102-86502012000200002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental canine model for sentinel lymph node biopsy in the vulva using technetium and patent blue dye

Abstract: PURPOSE: This paper aims to study and define the experimental model of sentinel lymph node biopsy of the vulva in bitches. METHODS: 0.2 ml of 99mTc phytate was injected intradermally, using a fine gauge insulin needle in the anterior commissure of the vulva. Thirty minutes after 99mTc injection, the inguinal mapping was performed using a gamma probe. After this, 0.5 ml of blue dye (bleu patenté V Guerbet 2.5%) was injected in the same place. After 15 minutes, a 3 cm long inguinal incision was made at point max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…From the first studies conducted by [17], which showed the method's efficiency for detecting mammary lymph nodes in female dogs, the technique has been used experimentally in canines, albeit timidly, in other anatomical locations, such as the vulva and the stomach [18] [19].…”
Section: Considerationsmentioning
confidence: 99%
“…From the first studies conducted by [17], which showed the method's efficiency for detecting mammary lymph nodes in female dogs, the technique has been used experimentally in canines, albeit timidly, in other anatomical locations, such as the vulva and the stomach [18] [19].…”
Section: Considerationsmentioning
confidence: 99%
“…An easy, convenient, safe, and low-cost technique for intraoperative identification of SLNs consists of the use of vital dyes (11,12). This technique shows high sensitivity and specificity and is primarily used in women.…”
Section: Introductionmentioning
confidence: 99%
“…This dye is widely used for human lymphatic mapping, for research, and for clinical purposes (Aquino et al 2012, Viehl et al 2013.…”
Section: Introductionmentioning
confidence: 99%